Advancing Soil Physics for Securing Food, Water, Soil and Ecosystem Services. Issue 1 (20th December 2018) - Shang, Jianying; Zhu, Qing; Zhang, Wei
Abstract : Core Ideas: Contributions are mainly from the 2017 International Soil Physics Workshop in China. Soils are fundamental in supplying food, energy, water (FEW), and ecosystem services. Interdisciplinary (convergence) approaches are needed to address FEW challenges. Soils are foundational to sustaining the food, energy, and water (FEW) systems and provide many essential ecosystem services. Soil degradation is a major threat to food security in China and elsewhere in the world. It is critical to advance soil science to improve the FEW systems so that FEW supplies can be provided to human populations in a sustainable and resilient manner. To do so, we must understand interactions among soil physical, chemical, and biological processes, as well as the role, function, and contribution of soil physical processes to delivering FEW supplies and ecosystem services. Soil processes and crop production are strongly controlled by physical processes such as soil water flow, aggregate stability, compaction, heat regime, irrigation and drainage, soil aeration, etc. Recognizing the importance of soil physics to the nexus of FEW systems, the collection in this special section mainly includes research presented at the International Workshop of Soil Physics and the Nexus of Food, Energy, and Water held on 3–5 Aug. 2017 at Shenyang, China. This special section covers diverse topics including fundamental soil physical properties and water flow, land use and agricultural management, soil organic carbon management, soil physical modeling, and transport of emerging contaminants. More future research using interdisciplinary (nexus or convergence) approaches should be undertaken to address challenges in many contemporary and emerging FEW issues.